Results of Selection of Winter Durum Wheat in the Republic of Moldova - Rotary, Silvia; Lyatamborg, Svetlana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
In such a way, using interspecific and intraspecific hybridizations, was created value sources of material for selection of hard winter wheat. By the way of repeated selections, there have been selected from hybrid combinations, highly productive and short – stalk lines which differ between them by high winter hardiness and other value economic and biological characters. All these lines have been studied into various experiences of the selection process (in breeding control and competitive nurseries). The grain yield of the best forms selected from various hybrids have varied from 3.4–4.4 t/ha that has been with 0.1–0.9 t/ha more than check variety. Because of work of many years, the plant breeder of our country has created new varieties of this valuable culture that are characterized by good winter hardiness, productivity and the resistance to mealy dew, rust and fusarial diseases. New varieties: Auriu 273, Hordeiforme 333, 335, 340, Auriu 1, 2, 3 are of interest for cultivation in the fields of Republic Moldova and as valuable donors in the process of hybridization and creation of new varieties. On the average, for 4 years the grain yield of these varieties was 3.1–4.9 t/ha. Characteristic of presented varieties was a good winter hardiness, average ripeness, resistance to diseases and to lodging, high technological indexes and others. They have a large grain of amber-yellow color containing a high percent of protein (13–15%) and gluten (25–30%). At present 4 (four) sorts (Auriu 273, Hordeiforme 333, 335, 340) are zoned in the Republic of Moldova. Our sorts and forms of hard winter wheat with high productivity have got a big practical value for selection in Moldova. Based on above said, it is possible to draw a conclusion that most of our sorts created by us can be used in crossings as sources and donors of one or a few economic valuable characters and features.